Pendampingan Manajemen Operasional Laboratorium (Tata Ruang) Pada Laboratorium Pendidikan IPA SMP 3 Arso, Kab. Keerom, Papua - Satar, Suriyah; Nurbaya, Nurbaya; Listiani, Hanida; Lodeh, Cartika Candra (Universitas Cenderawasih, 2024)
The application of the scientific method to science learning requires a laboratory as a means or place to carry out practical activities. Utilization of laboratories or practical activities is part of the teaching and learning process. To prevent and overcome problems that may arise in laboratory management, it is necessary to make good laboratory management efforts. Therefore, it is intended to carry out the actualization of laboratory principles in question, namely laboratory surgery in the context of optimizing the Science Education laboratory at SMP Negeri 3 Arso. This service is assistance in laboratory management carried out by Lecturers at the PMIPA Department, FKIP, Cenderawasih University. The subjects of service are teachers and students of SMP Negeri 3 Arso, while the object of service is the science education laboratory at SMP Negeri 3 Arso. Achievement of success in community service activities was achieved through distributing survey instruments to schools. The laboratory management assistance activities that have been carried out include inventory of practical equipment, creating a laboratory organizational structure, organizing and cleaning equipment rooms such as tool cabinets, practical rooms, practical tables, cleaning practical equipment, and creating rules for practical activities. This assistance received a positive response from the school which showed that the school's need for a good science laboratory was met.